2016
DOI: 10.1371/journal.pone.0165933
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis: A Nationwide Population-Based Study Using National Health Insurance Database in Korea

Abstract: BackgroundStevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are life-threatening diseases; however, it is hard to estimate their incidence due to the rarity of these diseases. We evaluated the incidence of SJS and TEN using a nationwide administrative database.MethodsWe used a national medical insurance review system (Health Insurance Review and Assessment) database which contained the claim data of the entire nation from 2009 to 2013 to estimate the accurate incidence of SJS and TEN in Korea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 29 publications
4
76
3
1
Order By: Relevance
“…Yang et al . noted that it was difficult to survey the real‐world incidences of SJS/TEN because of their rarity …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al . noted that it was difficult to survey the real‐world incidences of SJS/TEN because of their rarity …”
Section: Discussionmentioning
confidence: 99%
“…Although both Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare, they are potentially life‐threatening disorders characterized by widespread epidermal necrosis of the skin and mucosa . The incidences of SJS and TEN have been reported as 3.96–5.3 cases for SJS, and 0.4–1.45 cases for TEN, per million . Their classification is based on the body surface area (BSA) affected.…”
mentioning
confidence: 99%
“…4 Hospital-based studies and studies from large electronic databases have found an annual incidence of 1-13 cases per million individuals. [9][10][11][12][13][14] The overall mortality rate is usually reported to be between 10% and 20%. 4,9,[11][12][13] These wide estimate ranges may be explained by these studies using a unique source of data with their own inherent limitations or the selection of cases mostly based on disease codes with possible misclassification.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…SJS/TEN is rare, with an annual incidence of 1–6 per million for SJS and 0.4–1.45 per million for TEN . Groups at increased risk of developing SJS/TEN include those with immunosuppression, especially those with human immunodeficiency virus, slow acetylator genotypes, and individuals with specific HLA alleles …”
Section: Introductionmentioning
confidence: 99%